Managing cultural specificity and cultural embeddedness when internationalizing: Cultural strategies of Japanese craft firms - Sasaki, Innan; Nummela, Niina; Ravasi, Davide (Journal of International Business Studies, 2021)
When entering international markets, manufacturers of consumer products are expected to adapt their products in order to meet local consumption practices. Doing so is particularly challenging for producers of culturally-specific products—that is, products that are little known, understood, or valued outside their original cultural milieu—whose operations are often deeply embedded in local conventions and traditions. To examine how SMEs navigate tensions between the cultural specificity of products and the cultural embeddedness of operations when expanding internationally, we conducted a multiple case study of Japanese producers of heritage craft located in Kyoto. Our findings reveal three strategies available to address these tensions—namely, selective targeting, cultural adaptation, and cultural transposition—and highlight the pivotal role played by local distributors and foreign designers, serving as cultural intermediaries, in bridging systems of domestic and foreign cultural practices and meanings. Our findings portray product adaptation as an ongoing process that unfolds along with a firm’s international expansion, as producers and intermediaries explore ways to bridge cultural differences. They illuminate the lengthy processes of learning and unlearning, adjusting, and rethinking that underlie managers’ efforts to strike a balance between standardization and adaptation as they internationalize.